Strategic management in Slovak enterprises: A survey findings - Štefan Slávik (Journal for East European Management Studies, 2001)
The paper deals with exploring the level of strategic management in Slovak enterprises after nearly 10 years of transformation from centrally planned to the market economy. It evaluates selected parts of strategic management process considering both size categories of enterprises and several selected industries. It characterizes business environment in these industries and indicates how the enterprises in examined industries know their external environment and how they are able to orientate themselves within the environment. Practical result of this study is that it reveals the weaknesses in firm's strategic management in the period of transforming economy and identifies the possibilities of its further improvement. – – Der Artikel befasst sich mit dem Grad der strategischen Unternehmensführung in der Slowakei nach knapp zehn jahren Umwandlung zentral geplanter Wirtschaft in die Marktwirtschaft. Er bewertet ausgewählte Teile des strategischen Führungprozesses aus Sicht der Grössenkategorien der Unternehmen, und aus Sicht einiger ausgewählter Industriegebiete. Der Autor charakterisiert auf diesen Gebieten das unternehmerische Milieu, und weist darauf hin, wie stark die Unternehmen ihre externe Umgebung kennen, und wie sie sich darin orientieren. Das praktische Ergebnis der Studie zeigt Schwachstellen in der strategischen Unternehmensführung der sich umwandelnden Wirtschaft, und identifiziert Verbesserungsmöglichkeiten.
Keywords: 650